Questionnaire Development for the Evaluation of the Educational Web Site “Youth 2004” Examining the Perceptions of Senior High School Students - Vernadakis Νικόλαος; Tsitskari Ευστρατία; Kellis Ηρακλής; Tzetzis Γιώργος; Kioumourtzoglou Ευθύµης (Inquiries in Physical Education and Sport, 2003)
The purpose of this study was to develop a psychometric questionnaire in order to evaluate the educational web site “Youth 2004” considering the perceptions of Greek abroad students of Sydney. Τhe differences among the sex were also investigated. Participants were 192 high school students, between the ages from 15-17 years old. Data was collected using an on-line survey. Results from the factor analysis yielded five factors: “suitability for audience”, “appropriateness of information’s web format”, “easy to direct and be oriented”, “interaction and feedback” and “graphic and multimedia design”, accounting for 70.03% of the variance. Independent-samples t test analysis revealed no significant differences between the two sex groups when they come to evaluate any of the five factors. In conclusion, the student feedback from the questionnaires indicated a general level of satisfaction and contentment with this particular web site.